Theoretical and Methodological Analysis of Life Satisfaction Phenomenon as a Condition of Professional I-Concept Development - Kliuiko, Lesia (Psychological Prospects Journal, 2018)
The article deals with quality of life satisfaction as one of the main conditions of professional I-concept development. Satisfaction with the quality of life is determined, first of all, by the achieved targets, the overcoming of difficulties, changes taking place in personal and professional life, and the whole complex of features, associated with neuroticism is influenced by the level of life satisfaction. The article analyzes the latest studies concerning the phenomenon of life satisfaction in foreign and national literature, and the problems of the formation and development of the I-concept in the scientific works of psychologists are discussed. I-concept in the inner world of human-being, and its self-consciousness in particular, is an important structural component of psychological self-organization, which functions as a prerequisite and result of the social interaction effectiveness and quality of life as the whole, and it turns out to be a relatively well-established, dynamic and, to a certain extent, а conscious system of person’s representations. The article also presents a theoretical study of life satisfaction as one of the conditions for the development of a professional I-concept of personality and states that life satisfaction is a complex psychological concept. Different components and factors of life quality satisfaction are distinguished. I-concept is formed in the stages of socialization and has an individual-natural cause and arises in the process of deploying social interaction as a result of its cultural development, and therefore it is relatively stable and at the same time suited to internal oscillations and changes in mental neoplasm. In addition, the I-concept is described in terms of the content and nature of the ideas about oneself, the complexity and differentiation of these representations, their subjective importance for the individual, as well as the internal integrity, consistency, and sustainability in time.